Nanotechnology in Colorectal Cancer for Precision Diagnosis and Therapy - Brar, Basanti; Ranjan, Koushlesh; Palria, Ankur; Kumar, Rajesh; Ghosh, Mayukh; Sihag, Sweety; Minakshi, Prasad (Frontiers in Nanotechnology, 2021)
Colorectal cancer (CRC) is the third most frequently occurring tumor in the human population. CRCs are usually adenocarcinomatous and originate as a polyp on the inner wall of the colon or rectum which may become malignant in the due course of time. Although the therapeutic options of CRC are limited, the early diagnosis of CRC may play an important role in preventive and therapeutic interventions to decrease the mortality rate. The CRC-affected tissues exhibit several molecular markers that may be exploited as the novel strategy to develop newer approaches for the treatment of the disease. Nanotechnology consists of a wide array of innovative and astonishing nanomaterials with both diagnostics and therapeutic potential. Several nanomaterials and nano formulations such as Carbon nanotubes, Dendrimer, Liposomes, Silica Nanoparticles, Gold nanoparticles, Metal-organic frameworks, Core-shell polymeric nano-formulations, Nano-emulsion System, etc can be used to targeted anticancer drug delivery and diagnostic purposes in CRC. The light-sensitive photosensitizer drugs loaded gold and silica nanoparticles can be used to diagnose as well as the killing of CRC cells by the targeted delivery of anticancer drugs to cancer cells. This review is focused on the recent advancement of nanotechnology in the diagnosis and treatment of CRC.